The impact of depression, anxiety and comorbidity on occupational outcomes. (25th October 2021) - Deady, M; Collins, D A J; Johnston, D A; Glozier, N; Calvo, R A; Christensen, H; Harvey, S B
Abstract: Background: Anxiety and depression account for considerable cost to organizations, driven by both presenteeism (reduced performance due to attending work while ill) and absenteeism. Most research has focused on the impact of depression, with less attention given to anxiety and comorbid presentations. Aims: To explore the cross-sectional relationship between depression and anxiety (individually and comorbidly) on workplace performance and sickness absence. Methods: As part of a larger study to evaluate a mental health app, 4953 working Australians were recruited. Participants completed in-app assessment including demographic questions, the Patient Health Questionnaire-9, two-item Generalized Anxiety Disorder and questions from the World Health Organization Health and Work Performance Questionnaire. Cut-off scores were used to establish probable cases of depression alone, anxiety alone and comorbidity. Results: Of the total sample, 7% met cut-off for depression only, 13% anxiety only, while 16% were comorbid. Those with comorbidity reported greater symptom severity, poorer work performance and more sickness absence compared to all other groups. Presenteeism and absenteeism were significantly worse in those with depression only and anxiety only compared to those with non-clinical symptom levels. Although those with depression alone tended to have poorer outcomes than the anxiety-only group, when sample prevalence rates were considered, the impact on presenteeism was comparable. Conclusions: Workplace functioning is heavily impacted by depression and anxiety both independently and where they co-occur. While comorbidity and more severe depression presentations stand out as impairing, workplace interventions should also prioritize targeting of anxiety disorders (and associated presenteeism) given their high population prevalence.